2015
DOI: 10.18632/oncotarget.3505
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine induces autophagy and differentiation by activating ROS and Notch1 signaling in leukemia cells

Abstract: All-trans retinoic acid (ATRA) is a differentiating agent for the treatment of acute promyelocytic leukemia (APL). However, the therapeutic efficacy of ATRA has limitations. Tetrandrine is a traditional Chinese medicinal herb extract with antitumor effects. In this study, we investigated the effects of tetrandrine on human PML-RARα-positive acute promyelocytic leukemia cells. Tetrandrine inhibited tumors in vivo. It induced autophagy and differentiation by triggering ROS generation and activating Notch1 signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…It was demonstrated that tetrandrine induced autophagy in human hepatocellular carcinoma via mitochondrial dysfunction, ROS accumulation and activation of the extracellular signal-regulated kinase (ERK) signaling pathway (23). In addition, tetrandrine induced autophagy by triggering ROS generation and upregulating Notch1 signaling in acute premyelocytic leukemia cells (24). In contrast, tetrandrine was identified as a potent lysosomal deacidification agent to block autophagic flux in prostate cancer PC-3 and renal cell carcinoma 786-O cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that tetrandrine induced autophagy in human hepatocellular carcinoma via mitochondrial dysfunction, ROS accumulation and activation of the extracellular signal-regulated kinase (ERK) signaling pathway (23). In addition, tetrandrine induced autophagy by triggering ROS generation and upregulating Notch1 signaling in acute premyelocytic leukemia cells (24). In contrast, tetrandrine was identified as a potent lysosomal deacidification agent to block autophagic flux in prostate cancer PC-3 and renal cell carcinoma 786-O cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…It would be helpful to prevent the development of hepatocellular carcinoma in the high-risk group of patients with chronic hepatitis or cirrhosis. Natural health products have attracted extensive attention in health promotion and disease treatment including cancer [24]. In addition, natural product-based drug discovery is a major route leading to developing therapeutic drugs for various diseases including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of tetrandrine on NB4 leukemia cells in vivo and in vitro revealed that tetrandrine-induced differentiation is accompanied by autophagy from the accumulation of ROS and by Notch1 signaling activation. Furthermore, autophagy and differentiation were also induced by tetrandrine in M5 type patient primary leukemia cells [71]. Different from an autophagy activator, Qiu et al presented tetrandrine as a potent lysosomal inhibitor, blocking autophagic flux at the lysosomal degradation stage in tumor cells, predominantly by neutralizing lysosomal acidity and then decreasing the recycling of cellular fuels [72].…”
Section: Inducing Cancer Cell Autophagymentioning
confidence: 99%
“…On the other hand, the tetrandirne-induced autophagy may play a protective function and weaken apoptosis in tumor cells which provide an efficient approach to synergize apoptosis by pharmacologically inhibiting autophagy [71, 74, 75]. …”
Section: Inducing Cancer Cell Autophagymentioning
confidence: 99%